2016
DOI: 10.12693/aphyspola.129.661
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior of in-Situ AlB2/Al-Cu Metal Matrix Composite

Abstract: The aim of this study was to fabricate 30 wt.% AlB2/Al-Cu composites using in-situ casting processes and to investigate the corrosion behavior of the composites and of the matrix material in various media. The electrochemical parameters were obtained from potentiodynamic polarization curves. The composites were prepared by liquid reaction of aluminum matrix with boron oxide at 1400• C. The results show that the corrosion resistance of the composite was higher than that of the matrix in selected corrosion media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Saravanan et al [17] reported that the addition of cenosphere will reduce corrossion rate for Alumnium 6063 metal matrix composites. Falcon et al [12] made a study that the presence of TiC particles in Mg-Aluminium alloy composites will increase the corrossion resistance. Elcicek et al [11] reported that addition of AlB 2 in Al-Cu alloy metal matrix will reduce the corrossion rate of the composites.…”
mentioning
confidence: 99%
“…Saravanan et al [17] reported that the addition of cenosphere will reduce corrossion rate for Alumnium 6063 metal matrix composites. Falcon et al [12] made a study that the presence of TiC particles in Mg-Aluminium alloy composites will increase the corrossion resistance. Elcicek et al [11] reported that addition of AlB 2 in Al-Cu alloy metal matrix will reduce the corrossion rate of the composites.…”
mentioning
confidence: 99%